Goliath - Westerfeld, Scott; Thompson, Keith 1982- (New York Simon Pulse, 2011)
Alek and Deryn encounter obstacles on the last leg of their round-the-world quest to end World War I, reclaim Alek's throne as prince of Austria, and finally fall in love.
Sequel to: Behemoth.
Col. ill. on lining papers.
790L
Keywords: Animals, Mythical; Princes; War stories; Genetic engineering; Imaginary creatures; Princes; War; Genetic engineering; Science fiction; Young adult fiction